2018
DOI: 10.1021/acsabm.8b00011
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Properties of Diamondoid-DNA Complexes

Abstract: DNA sensing with engineered nanomaterials can bestow a new platform for single nucleotide identification and sequencing. Nevertheless, understanding the relevant nano-bio interfaces can provide a wealth of information on structures, energetics, and dynamics with a great potential in molecular nanotechnology. Herein, we explore the sensitivity of DNA units, the nucleotides, with a tiny probe, the diamond-like structures known as diamondoids. The probe diamondoid and the target nucleotides interact via hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The electronic energy gap on the x-axis is given in units of eV. charge transfer behavior between the diamondoid and the nucleotides was found to correlate to the nature of the hydrogen bonding in the complex and the location of the frontier molecular orbitals Sarap et al ( 2018) 72 . In order to visualize the charge dynamics within the diamondoid-nucleotides, in Figure 4(a), representative results for the two configurations in the case of T and C are with memS are shown.…”
Section: Nucleotide -Diamondoid Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…The electronic energy gap on the x-axis is given in units of eV. charge transfer behavior between the diamondoid and the nucleotides was found to correlate to the nature of the hydrogen bonding in the complex and the location of the frontier molecular orbitals Sarap et al ( 2018) 72 . In order to visualize the charge dynamics within the diamondoid-nucleotides, in Figure 4(a), representative results for the two configurations in the case of T and C are with memS are shown.…”
Section: Nucleotide -Diamondoid Bindingmentioning
confidence: 99%
“…Independent of the type of diamondoid or nucleotide used, hydrogen binding energies in the range �5-15 kcal/ mol were calculated and lie between physisorption and chemisorption. The hydrogen bonding is formed by one up to three hydrogen bonds, depending on the binding arrangements Sarap et al (2018) 72 . The charge dynamics in the complexes can be observed in the femtosecond scale and depend on the relative arrangement of the molecules and the nucleotide identity.…”
Section: Nucleotide -Diamondoid Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was found that the size of the diamondoids can affect the melting temperature of the DNA [161]. These findings have initiated a number of theoretical studies [162][163][164][165][166][167][168][169] on exploring the possibility of using diamondoid-based 3D nanoarchitectures in the field of bionanotechnology [170], such as new biosensors with high sensitivity [162].…”
Section: Biological and Medical Applicationsmentioning
confidence: 99%
“…The integration of hydrogen bond interactions in polymeric materials results in supramolecular programmable, stimuli responsive architectures with captivating optoelectronic, 1,2 mechanical, 3,4 self-assembled 5–7 and thermal properties, 6,8 which is inspired by nature. These noncovalent interactions are crucial in biological systems, for example for stability reasons of secondary, tertiary and quaternary structures of proteins or for the molecular self-assembly of nucleic acids based on the complementary base pairing property.…”
Section: Introductionmentioning
confidence: 99%